UMPSA Open Day enlivens Jom Masuk U 2024 East Zone II - Nor Salwana, Mohammad Idris (UMPSA, 2024)
GAMBANG, 1 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) will hold an Open Day in conjunction with the Jom Masuk U 2024 East Zone II programme on 1 and 2 June at the UMPSA Sports Complex Hall of the Gambang Campus.